PERGESERAN PEKERJAAN REMAJA DARI SEKTOR PERTANIAN KE SEKTOR INDUSTRI - Sari, Meryyana Puspita; Suka Arjawa, I Gusti Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT The changing of socio-economic condition of adolescents, the demands of economy, job opportunities, income, as well as the living environment are the background of teenagers (18-21 years old) experiences in job shift in Muncar, Banyuwangi. Working in the sector of the food industry and processing of fish, cause the less of intensive job in agricultural thereforeÂ its open up housewives opportunity to work as a replacement of teenager labourÂ in the agricultural sector. The puspose of this study is to investigatc the job shift by the teenagers from agricultural to industrial sector and also to know the background of jobs shift from agriculture and the impact caused by the abandonment of the agricultural sector. This study uses qualitative method and case study approach, with interative analysis Miles and Huberman. The result shows that the long harvest time, the uncertain income, and farming as seasonal work, as well as the environment which in Muncar in industrial area of the teenagers job shifts. The job shifts done by the teenagers have made and impact over agricultural sector, in which it has been abandoned by the teenagers. The discontinuation of farming labour resulting less workers so its open up jobs for women the opportunities to replace sharecroppers in working at farmland. Max Weberâ€™s theory of social action is used to analyze the result of the research especially in social action, value action, and affective action. Keywords: shift work, youth, the agricultural sector, industrial sector